Municipal acute care teams as a flexible solution for the treatment of acutely ill patients at-home: a mixed-method study of patients’ and caregivers’ experiences with an acute care team - Annmarie Touborg Lassen; Christina Østervang; Stine Emilie Junker Udesen; Dorthe Susanne Nielsen; Nina Andersen (BMJ Open)
Objective Development of initiatives to reduce hospitalisations is a major focus of healthcare planning. Strengthening the community with municipal acute care teams or units is a newly implemented Danish initiative aimed at preventing hospitalisations and supporting more flexible services. This study aims to describe patients treated by a municipal acute care team and to explore patients’ and caregivers’ experiences with at-home treatment.Design A mixed-method study consisting of descriptive statistics of patients treated by an acute care team, and quantitative and qualitative data from follow-up telephone questionnaires with patients and caregivers.Setting The acute care team, ‘Acute Team Odense’ (ATO), in the Odense Municipality, Denmark.Participants Patients treated by ATO and their caregivers. ATO treated 3231 patients (5676 contacts) in the period of 2018–2019.Results Average number of new contacts per day was 7.8, and the median treatment-length was 1 day. Patients were referred by various healthcare providers and most often by general practitioners, municipal staff and hospital staff. The median age of the patients was 80 years, and 20% were independent before the treatment. In total, 787/5676 contacts received at-home intravenous therapy, which corresponded to 3.6 hospital beds saved per day. The questionnaires were completed by 307/478 patients and 168/254 caregivers. Most respondents stated they would prefer at-home treatment in future similar situations as it enabled them to maintain their lives. Several respondents also experienced that ATO avoided hospitalisations or reduced hospital stays, which was described as a relief.Conclusion ATO was frequently used, indicating the demand for community-based acute healthcare. The patients and caregivers experienced that this solution avoided hospitalisations and allowed them to maintain their lives, and this was described as less burdensome. As a result of these findings, this initiative has been continued with an ongoing focus on searching for possibilities aimed to prevent hospitalisations.